Implementation of Sustainable Development Goals (SDGs) in Sustainable Regional Development in Muara Enim Regency - Hardiana, Raden Dian; Sugiharti, Harpa; Mulyani, Heni; Kurniati, Fitrina; Arlinda, Hanifia; Lhutfi, Iqbal (Universitas Pendidikan Indonesia, 2024)
The purpose of monitoring is to observe the progress of achieving the Sustainable Development Goals (SDGs) over time to measure progress in achieving targets using predetermined indicators and identify and anticipate problems that arise and will arise so that action can be taken as early as possible. The evaluation provided an overview of the achievements of SDGs. It analyses the problems and factors that cause them so that the evaluation results become feedback for improving policy planning, programs, and activities, especially those related to SDGs. The results of the implementation of this Community Service show that the number of Muara Enim Regency SDGs indicators contained in the SDGs Regional Action Plan document are 153 indicators, consisting of 70 indicators of the social development pillar, 37 indicators on the economic development pillar, 29 indicators on the environmental development pillar and 17 indicators on the legal / governance development pillar. Many indicators still fall into the category of unmeasurable or purple. Then, there are still indicators in the red and yellow categories due to the setting of targets that are pretty high and different from the targets in other planning documents and even with higher targets and no revision or change in targets, especially after the COVID-19 pandemic in 2020.